PERAN INSPEKTORAT KABUPATEN : HARAPAN DAN TANTANGAN (Studi Kualitatif Pada Inspektorat Pemerintah Kabupaten Kepulauan Meranti) - Tyara Miranda; Amir Hasan; M. Rasuli (PEKBIS, 2019)
The objective of this study is to evaluate the role of the Inspectorate of KabupatenKepulauan Meranti as an internal watchdog of government officials and know theexpectations and challenges for APIP in the future. The type of research used in thisstudy is qualitative research with grounded theory approach. The data used in thisstudy include primary data and secondary data, such are observation, in-depthinterview, literature study and documentation. The result of the research shows thatthe role of Inspectorate of Kabupaten Kepulauan Meranti as an internal supervisoryapparatus of government has been run well although not yet optimal because thereare some obstacles such as limited number of human resources, budgetrationalization and inadequate facilities and infrastructures. Nevertheless, the resultsof internal control conducted by the Inspectorate of Kabupaten Kepulauan Merantihave been reliable and utilized by stakeholders. Expectations for APIP in the futureare the increasing number of professional human resources, the increasing ofincome allowance, adequate facilities and infrastructure, the increasing of APIP staffcompetence, budget availability, leadership commitment, APIP become the third lineof defenses, clarity of roles, institutional improvement, synergy between BPKP andthe inspectorate, the existence of performance measurement systems, and theemergence of positive public participation. The challenges for APIP in the future areto balance the role of assurance and consulting, utilization of information technology,finding a way how to recover losses, follow up potential losses, improveprofessionalism and integrity, reliable reports, maintain the quality of governance,expanding knowledge, optimize the supervision of five prone areas corruption,providing recommendations that have a deterrent effect, breaking the 'lame'inspectorate stigma and increasing APIP's capability to level 5.